Antimicrobial Susceptibility and Clinical Findings of Anaerobic Bacteria - Fernando Cobo (MDPI AG, 2022)
Anaerobic microorganisms are the most abundant components of the normal human microbiota; they colonize mucous membranes such as the oral cavity and the gastrointestinal and female genital tracts, and they are common pathogens in human populations [...]